Dermoscopy as a Tool in Differentiating Cutaneous Squamous Cell Carcinoma From Its Variants - Dimitrios Sgouros; Melpomeni Theofili; Vasileia Damaskou; Sofia Theotokoglou; Konstantinos Theodoropoulos; Alexander Stratigos; Panagiotis Theofilis; Ioannis Panayiotides; Dimitrios Rigopoulos; Alexander Katoulis (Mattioli1885, 2021)
Background: Dermoscopic features of cutaneous squamous cell carcinoma (cSCC) have been widely studied, but their accuracy should be further investigated. Objectives: This study assessed the diagnostic accuracy of a set of predetermined dermoscopic structures for 3 variants of cSCC, namely Bowen disease, keratoacanthoma and invasive cSCC. Methods: Dermoscopic images of 56 histopathologically confirmed cSCC lesions (9 Bowen disease lesions, 7 keratoacanthomas, and 40 invasive cSCCs) were examined, and the diagnostic accuracy of dermoscopic structures was assessed. Discriminative ability of statistically significant positive predictors was determined using receiver operating characteristic (ROC) curves, and defined as an area under the ROC curve >0.700. Results: Dermoscopic structures with statistical significance and discriminative ability were: for Bowen disease, clustered glomerular vessels and erosions; for keratoacanthoma, a central keratin plug; and for invasive cSCC, a mixed color of the background. Clustered and glomerular vessels had, for Bowen disease, perfect diagnostic accuracy, with: sensitivity of 88.9% for both features; specificity of 97.9% and 93.6%, respectively; positive predictive value (PPV) of 88.9% and 72.7%, respectively; and negative predictive value (NPV) of 97.8% for both. Erosions had, for BD, high specificity (87.2%) and NPV (91.1%), but low sensitivity (55.6%) and PPV (45.5%). A central keratin plug had, for keratoacanthoma, high specificity (87.8%) and NPV (93.5%), but low sensitivity (57.1%) and PPV (40%). A mixed background color had, for invasive cSCC, high specificity (81.3%) and PPV (89.7%), but low sensitivity (65%) and NPV (48.2%). Conclusion: Dermoscopy accurately differentiates BD, through clustered glomerular vessels, from keratoacanthoma and invasive cSCC. Dermoscopic structures of keratoacanthoma and invasive cSCC overlap, and only histopathologic analysis differentiates them precisely.